Student-Centered Learning and Collaborative Learning in Arabic Language Education - M. Safarul Khair; Satriawan (Pascasarjana Universitas Islam Negeri Mataram, 2025)
This study explores the implementation of Student-Centered Learning (SCL) and Collaborative Learning (CL) in the context of Arabic language education. As educational paradigms shift from traditional teacher-centered approaches to more interactive and learner-driven methods, the need to understand and apply SCL and CL becomes increasingly relevant. Through a qualitative descriptive approach, this research reviews literature and educational practices that demonstrate how these two strategies contribute to improving learner engagement, autonomy, communication skills, and critical thinking in Arabic classrooms. The findings indicate that integrating SCL and CL not only enhances the effectiveness of Arabic language acquisition but also encourages active participation and cooperative problem-solving among students. However, challenges such as classroom management and unequal student involvement require careful planning and teacher facilitation. The study concludes by emphasizing the importance of these approaches in modern language pedagogy and provides recommendations for future research and classroom implementation.